2021
DOI: 10.1038/s41598-021-87870-z
|View full text |Cite
|
Sign up to set email alerts
|

Selection of nitrogen responsive root architectural traits in spinach using machine learning and genetic correlations

Abstract: The efficient acquisition and transport of nutrients by plants largely depend on the root architecture. Due to the absence of complex microbial network interactions and soil heterogeneity in a restricted soilless medium, the architecture of roots is a function of genetics defined by the soilless matrix and exogenously supplied nutrients such as nitrogen (N). The knowledge of root trait combinations that offer the optimal nitrogen use efficiency (NUE) is far from being conclusive. The objective of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
0
17
0
1
Order By: Relevance
“…The seeds of each accession were sown in triplicate in turface (Turface Athletics MVP, PROFILE Products LLC, Buffalo Grove, Illinois, USA) in small pots (10.2 cm × 10.2 cm and 8.9 cm deep) following a randomized complete block design. Additional details of the experimental set-up are detailed previously 11 . Plants were fertilized with two concentrations of N, low N (LN; 50 ppm), and high N (HN; 200 ppm) using Peters® professional ready mix (5-11-26, hydroponics special water-soluble fertilizer, Everris NA Inc., Ohio, U.S.A.) after seedling emergence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The seeds of each accession were sown in triplicate in turface (Turface Athletics MVP, PROFILE Products LLC, Buffalo Grove, Illinois, USA) in small pots (10.2 cm × 10.2 cm and 8.9 cm deep) following a randomized complete block design. Additional details of the experimental set-up are detailed previously 11 . Plants were fertilized with two concentrations of N, low N (LN; 50 ppm), and high N (HN; 200 ppm) using Peters® professional ready mix (5-11-26, hydroponics special water-soluble fertilizer, Everris NA Inc., Ohio, U.S.A.) after seedling emergence.…”
Section: Methodsmentioning
confidence: 99%
“…Enhancing the NUE in spinach by exploiting genetic diversity in the leaf traits has been proposed 9 , 10 . We have previously shown that using a uniform soil-less matrix allowed us to use the supervised machine learning algorithm to predict the importance of root traits in spinach 11 . Biomass allocation among above (leaves) and below-ground (roots) organs is influenced by N uptake and distribution, which have crucial impacts on plant growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Roots architecture is crucial for uptake and supply N and other nutrients. Indeed, root traits such as root length, root tips, root average diameter, root weight, and specific root length were crucial determinants for NUE under low N conditions in wheat and spinach ( Awika et al, 2021 ; Puccio et al, 2021 ). However, information on different root trait combinations related to NUE in sorghum warrants further research.…”
Section: Sensor-based High-throughput Phenotyping For Determining Nit...mentioning
confidence: 99%
“…The phenotypic consequence of a change in nutrient supply in a given genotype depends on exact nutrient concentration, nutrient distribution and gradients, concentrations of other nutrients, developmental stage of the plant, and environmental factors [43]. Awika et al [44] tested baby spinach accessions in small pots to determine phenotypic and genetic correlations between root traits and the shoot fresh weights under low and high nitrogen concentrations. They also found that, in a restricted soilless medium, the architecture of roots is a function of genetics defined by the soilless matrix and exogenously supplied nutrients.…”
Section: Nutrient Solutionmentioning
confidence: 99%